Effects of ginseng berry saponins on cardiorespiratory fitness in patients with SCAD: a randomized, double-blinded, placebo-controlled trial - Ge, Yaru; Huan, Na; Sun, Jinghui; Chao, Tiantian; Zhao, Xiaohui; Wang, Chenglong (Frontiers in Pharmacology, 2026)
BackgroundWith the development of cardiac rehabilitation (CR), the advantages of combined Chinese and Western medicine cardiac rehabilitation for the treatment of stable coronary artery disease (SCAD) have become increasingly prominent.PurposeThis study was aimed to evaluate the effect of Zhenyuan capsule (a Chinese patented medicine consisting of ginseng berry saponins extracted from the mature berry of Panax Ginseng) on cardiorespiratory fitness (CRF) in patients with SCAD, and explore possible potential candidate molecule.Study Design and MethodsUsing a randomized, double-blind, placebo-controlled trial design, 100 patients with SCAD were enrolled and randomly divided into the group taking Zhenyuan capsules (test group, n = 50) and the group taking placebo (control group, n = 50). In both groups, patients were treated with secondary prevention medication for CHD, with the addition of 2 capsules of Zhenyuan capsule 3 times a day for 12 weeks in the test group and 2 capsules of placebo 3 times a day for 12 weeks in the control group, with a follow-up of 1 month after the end of treatment. Subjects completed symptom-limited maximal cardiopulmonary exercise test (CPET) on a bicycle ergometer at 3 time points before enrollment, after 12 weeks of treatment, and after 1 month of follow-up. The main outcome was the increase in metabolic equivalent.ResultsBoth at anaerobic threshold (AT) level and at maximal level, the results of between-group comparisons showed that the test group was significantly better than that of the control group after treatment (AT level: 0.58 ± 0.89 Mets vs. 0.15 ± 1.06 Mets; maximal level: 0.69 ± 0.92 Mets vs. 0.19 ± 0.93 Mets) (P < 0.05). No serious adverse events occurred in patients in both groups. Serum proteomics studies suggested that insulin-like growth factor II (IGF2) was downregulated in a minority of responders, potentially related to cholesterol metabolism and the PI3K-Akt pathway.ConclusionZhenyuan capsule can significantly improve the CRF of patients with SCAD, and the downregulation of IGF2 observed in a minority of responders suggests IGF2 may be a potential candidate molecule of interest associated with cholesterol metabolism and the PI3K-Akt pathway.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=53361, identifier ChiCTR2000032818.